2018
DOI: 10.18203/2320-6012.ijrms20185098
|View full text |Cite
|
Sign up to set email alerts
|

Intrastromal antifungal injection as a successful modality of treatment for fungal keratitis: a case series

Abstract: Fungal keratitis is a dreaded occurrence in the cornea and anterior segment given the difficulty in treating the disease. Hereby reporting 5 cases of fungal keratitis causes by virulent organisms such as Aspergillus versicolor, Aspergillus fumigatus, Phialophora sp, and Fusarium sp. A retrospective interventional case series of 5 fungal keratitis which were successfully treated by intrastromal antifungal injection performed by a single surgeon from March 2017 till April 2018. The fungal keratitis stromal absce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…Another study showed improvement in 14 out of 20 patients, which required 2.65 injections on average [14]. It is important to mention that no adverse effects of intrastromal voriconazole application in a form of corneal haze, edema, erosions, and toxicity, which was consistent with cases from other studies [8].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Another study showed improvement in 14 out of 20 patients, which required 2.65 injections on average [14]. It is important to mention that no adverse effects of intrastromal voriconazole application in a form of corneal haze, edema, erosions, and toxicity, which was consistent with cases from other studies [8].…”
Section: Discussionsupporting
confidence: 81%
“…The limitation of topical antifungal medications is their poor penetration due to their high molecular size and toxicity [7] that leads to suboptimal results of the treatment. Many studies proved the efficacy of combined topical and systemic antifungal medications in the early stages of keratitis [8]. This led to the need of finding alternative methods of reaching the fungi with the intracameral and intrastromal application.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further complicating its management, significant antimicrobial resistance is often identified among one or more of the causative organisms [ 2 ]. While intrastromal injection of antimicrobial agents has garnered increased attention in the treatment of fungal keratitis refractory to topical therapy [ 4 , 5 , 6 , 7 ], the utility of this approach is still uncertain [ 8 , 9 ], and intrastromal antibiotic injection to treat bacterial keratitis is even less well established. To the best knowledge of the authors, examples of successful treatment of bacterial keratitis with intrastromal antibiotic injection in the literature are limited to a handful of case reports [ 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%